2022
DOI: 10.1002/ejoc.202200945
|View full text |Cite
|
Sign up to set email alerts
|

Domino Reactions through Recursive Anionic Cascades: The Advantageous Use of Nitronates

Abstract: Recursive Anionic Cyclization (RAC) continues to proliferate as a mechanistically distinct domino strategy. Deployment of nitroalkanes as a source of recursive carbanions has created a niche operating space for generating molecular complexity and diversity. This new corollary i. e. recursive nitronate cyclization is the basis of a domino [5 C+1 C] cyclization strategy wherein nitroalkanes act as one‐carbon lynchpin, providing rapid access to topologically intriguing, densely functionalized carbo‐ and heterocyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 175 publications
0
3
0
Order By: Relevance
“…In our previous reports, we have shown that new chiral ligands with good performance could be obtained via the combination of binaphthyl 8 and proline 9 moieties. For example, chiral ligands 1 showed good performance in enantioselective addition of diethylzinc to different aldehydes.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous reports, we have shown that new chiral ligands with good performance could be obtained via the combination of binaphthyl 8 and proline 9 moieties. For example, chiral ligands 1 showed good performance in enantioselective addition of diethylzinc to different aldehydes.…”
Section: Resultsmentioning
confidence: 99%
“…Intrinsic to such an approach is the possibility of execution in one flask operation through tandem/domino processes which in turn minimize the number of follow-on and work-up steps. The expected outcome from such tactics would be the expeditious delivery of complex, functionally embellished polycyclic scaffolds with reduction in the number of chemical and operational interventions …”
Section: Introductionmentioning
confidence: 99%
“…Among the choices available for multifunctional partners for engaging diynone 1 , table top dimethyl-1,3-acetone dicarboxylate (DMAD) with two active methylene sites appeared to offer attractive possibilities as it could trigger a base mediated tandem reaction cascade through either Michael–Michael or Michael–anti-Michael additions to diynones. The anticipated outcomes (not counting the possible reactivity of the two methylene derived anions undergoing Michael additions in recursive mode), providing access to fully functional eight- or seven-membered-ring products in a one-pot operation, appeared to be an alluring prospect as depicted in Scheme , and such possibilities have some precedence in the recently observed reactivity of diynones . The reaction between diynones and DMAD chartered deviant, albeit new and interesting courses as displayed in Scheme , leading either to multifunctional arenes 8 or furan-3­(2 H )-ones 9 depending on the reaction conditions.…”
mentioning
confidence: 97%